Characterization of copper sulfide hexananoplates, and nanoparticles synthesized by a sonochemical method - Phuruangrat A. (2014)
CuS hexanoplates and nanoparticles were prepared by sonochemical method in ethylene glycol as a solvent for 5 h. The products were characterized by X-ray diffraction (XRD), Raman spectroscopy, transmission electron microscopy (TEM), and energy dispersive X-ray (EDX) analysis. X-ray diffraction patterns detected only pure hexagonal CuS phase. Raman spectra show peaks at 473 cm-1, corresponding to the lattice vibration mode of S-S. Their morphologies were investigated by transmission electron microcopy, and the stoichiometric formula was also quantified.